Effects of dietary inclusion of dry distillers grains with solubles on performance, carcass characteristics, and nitrogen metabolism in meat sheep: a meta-analysis - Chelkapally, Sai Chandan; Terrill, Thomas H.; Estrada-Reyes, Zaira M.; Ogunade, Ibukun Michael; Pech-Cervantes, Andres Alfredo (Frontiers in Veterinary Science, 2023)
We conducted a meta-analysis in this scientific study to determine the effects of feeding meat sheep dry distillers grains with solubles (DDGS). Thirty-three peer-reviewed articles that met our inclusion requirements and were published between 1997 and 2021 were examined. To calculate the variation in performance, fermentation, carcass features, and nitrogen efficiency between the DDGS and control (no DDGS) treatments, we used 940 sheep weighing an average of 29.1±1.5 kg. We used a hierarchical mixed model to conduct a meta-regression, subset, and dose-response analysis, while taking into consideration categorical variables like breed (pure or cross-breed), and continuous factors, like CP, NDF, and DDGS inclusion rate. Our findings indicate that sheep fed DDGS had higher (P < 0.05) final body weight (51.4 vs. 50.4 kg), neutral detergent fiber digestibility (55.9 vs. 53.8%), and total-tract ether extract digestibility (81.7 vs. 78.7%) than sheep on a control diet. No effects were observed on DMI, CP, and rumen fermentation, but dietary DDGS tended to increase (P = 0.07) HC weight (25.53 vs. 24.6 kg) and meat (redness) color (16.6 vs. 16.3) among treatment comparisons. Dietary DDGS was associated with higher N intake (29.9 vs. 26.8 g/d), fecal N (8.2 vs. 7.8 g/d), and digestibility (71.9 vs. 68.5%). Urinary nitrogen was significantly (P < 0.05) affected linearly by increasing the intake of DDGS in the diet. Based on the dose-response analysis, dietary DDGS inclusion shouldn't exceed 20% to avoid negative effects on performance, nitrogen metabolism, and meat color. Dietary protein from DDGS should not exceed 17% to prevent reduced TVFA concentrations. Breed strongly influenced (P < 0.05) RMD in performance, and inconsistent responses were observed between crossbreed and purebred sheep comparisons. Despite these inconsistencies, no publication bias was observed, but a high variance (Ω2) among comparisons-between-studies was detected. This meta-analysis showed evidence in support of the hypothesis that feeding meat sheep DDGS at a rate of 20% can improve their performance, digestibility, carcass weight, and meat color.